Superhydrophobic Terrestrial Cyanobacteria and Land Plant Transition - Barthlott, Wilhelm; Büdel, Burkhard; Mail, Matthias; Neumann, Klaus Michael; Bartels, Dorothea; Fischer, Eberhard (Frontiers in Plant Science, 2022)
Plants and other organisms have evolved structures and mechanisms for colonizing land since the Early Ordovician. In this context, their surfaces, the crucial physical interface with the environment, are mainly considered barriers against water loss. It is suggested that extreme water repellency (superhydrophobicity) was an additional key innovation for the transition of algae from water to land some 400 mya. Superhydrophobicity enhances gas exchange on land and excludes aquatic competitors in water films. In a different context, in material science and surface technology, superhydrophobicity has also become one of the most important bioinspired innovations enabling the avoidance of water films and contamination. Here, we present data for an extremely water-repellent cyanobacterial biofilm of the desiccation tolerant Hassallia byssoidea providing evidence for a much earlier prokaryotic Precambrian (ca. 2.5 bya) origin of superhydrophobicity and chemical heterogeneities associated with land transition. The multicellular cyanobacterium is functionally differentiated in a submerged basal hydrophilic absorbing portion like a “rhizoid” and an upright emersed superhydrophobic “phyllocauloid” filament for assimilation, nitrogen fixation, and splash dispersed diaspores. Additional data are provided for superhydrophobic surfaces in terrestrial green algae and in virtually all ancestral land plants (Bryophytes, ferns and allies, Amborella, Nelumbo), slime moulds, and fungi. Rethinking of superhydrophobicity as an essential first step for life in terrestrial environments is suggested.